Prejudices against the unemployed – empirical evidence from Germany - Christiane Gross; Thomas Gurr; Monika Jungbauer-Gans; Sebastian Lang (Journal for Labour Market Research, 2020)
Prejudices against the unemployed pose an enormous threat to their self‑confidence and can make it difficult for them to re‑enter the labour market, resulting in further long‑term unemployment. Given these high costs for the unemployed and for society as a whole, our knowledge of prejudices against the unemployed is surprisingly scarce. We focus on the question of what determines the strength of prejudice among employees. By applying social identity theory, we assume that people who are disadvantaged in the labour market in general, also hold stronger prejudices. In addition, we assume that social status mediates this association and that self‑efficacy moderates it. We use data from the German panel study "Labour Market and Social Security" (PASS) and show that some groups of people who are themselves disadvantaged in the labour market (women and first‑generation immigrants) have more prejudices against the unemployed; however, people with poor mental health have even fewer prejudices. Low social status (in terms of educational background, income, and job status) is associated with strong prejudices; however, social status does work as mediator to a minor degree only. People with low self‑efficacy in general (main "effect") and first‑gener‑ation immigrants in particular (moderating "effect") have stronger prejudices. These results can be a starting point for developing measures to reduce prejudice and for the onset of a debate about the origins of prejudices against the unemployed.
Keywords: J15; J64; J71; E24; 330; Attitudes; Prejudice; Stereotype; Stigma; Unemployment